Proteomics Indicates Lactate Dehydrogenase Is Prognostic in Acetaminophen-Induced Acute Liver Failure Patients and Reveals Altered Signaling Pathways. (16th February 2022) - Vazquez, Joel H; Kennon-McGill, Stefanie; Byrum, Stephanie D; Mackintosh, Samuel G; Jaeschke, Hartmut; Williams, D Keith; Lee, William M; Dranoff, Jonathan A; McGill, Mitchell R; ,
Abstract: Better biomarkers to predict death early in acute liver failure (ALF) are needed. To that end, we obtained early (study day 1) and later (day 3) serum samples from transplant-free survivors ( n = 28) and nonsurvivors ( n = 30) of acetaminophen-induced ALF from the NIH-sponsored Acute Liver Failure Study Group and from control volunteers ( n = 10). To identify proteins that increase early in serum during ALF, we selected individuals from this cohort for whom alanine aminotransferase was lower on day 1 than day 3, indicating a time point before peak injury ( n = 10/group). We then performed untargeted proteomics on their day 1 samples. Out of 1682 quantifiable proteins, 361 were ≥ 4-fold elevated or decreased in ALF patients versus controls and 16 of those were further elevated or decreased ≥ 4-fold in nonsurvivors versus survivors, indicating potential to predict death. Interestingly, 1 of the biomarkers was lactate dehydrogenase (LDH), which is already measured in most clinical laboratories. To validate our proteomics results and to confirm the prognostic potential of LDH, we measured LDH activity in all day 1 and 3 samples from all 58 ALF patients. LDH was elevated in the nonsurvivors versus survivors on both days. In addition, it had prognostic value similar to the model for end-stage liver disease and outperformed the King's College Criteria, while a combination of model for end-stage liver disease and LDH together outperformed either alone. Finally, bioinformatics analysis of our proteomics data revealed alteration of numerous signaling pathways that may be important in liver regeneration. Overall, we conclude LDH can predict death in APAP-induced ALF.